The East Asian Metis in Francophone Literatures of the South Pacific, Indian Ocean, and North America - Ireland, Benjamin (2017)
This dissertation’s multi-sited historical and literary approach assesses how Asiatic cultural specificities ranging from foodways to indentured servitude frame the ways in which East Asian authors regard cross-cultural contact. In four chapters, I examine little-known literary works by East Asian métis writers, including Ook Chung (Korea/Japan/Canada), Dany Dalmayrac (Japan/New Caledonia), Jimmy Ly (China/Tahiti), and Daniel Honoré (China/La Réunion), who recount their multicultural identities, tribulations, and autobiographies in French. On the one hand, this analysis shows how postcolonial Franco-Asian literature has shaped the literary landscapes of the Francophone South Pacific through Japanese and Chinese writers of French. On the other, from a literary perspective, this dissertation affirms that mixed-raceness is not a methodology in itself, but rather a thematic through which authors create a methodology to analyze violence, memory, and kinship. Francophone East Asian authors of hyphenated origins offer in their novels methods to broach these thematics by placing into contiguity mixed-raceness and various cultural phenomena. This dissertation argues that mixed-race or métis East Asian migrants residing in the Francophone regions of Oceania, the Indian Ocean, and the Americas gave expression to new cultures of thought and movement, forging interethnic bonds between indigenous, intra-Asian Pacific, African, and French populaces during the nineteenth and twentieth centuries. I retrace the respective East Asian diasporas of Chinese and Japanese migrants across the Pacific Ocean before offering an analysis of their assimilation histories, as well as the ramifications that result from intra-Asian, Afro-Asian, and/or Franco-Asian interactions in these Francophone regions. I examine in addition post-Second World War Japanese migrant deportation and incarceration in New Caledonia and Australia, as well as the role mixed-race youth played in preserving a Japanese New Caledonian culture in the Francophone South ...